Diagnóstico fitosanitario en bosques implantados de Tectona grandis (Teca) en la zona de Balzar, Provincia del Guayas. - Flores Velastegui, Tonny Marlon (2005)
The present research was carried out in four faros belonging to Empress Tropibosques S.A. located in Balzar, Guayas Province, Ecuador. The results obtained show that during the raing season, leave eater insects attack Atta sp. (Hym.: Formicidae), sap suckers, Oncometopia sp. (Hom.: Cicadellidae), Spitters, Aeneolamia postica (Hem.-hom.: Cercopidae), Aphid_plant lice, Hyadaphis erysimi (Hem.-Hom.: Aphydidae); bedbugs, Zelus nugax (Hem.-Hete.: Coreidae), blck-bedbugs, Nesara sp. (Hem.: Pentatomidae); bark drillers, Scolytus sp. (Col.: Scarabaeidae); In addition to theses harmful insects, the presence of other pests of minor importance, which belong to Cantharidae, Lampiridae, Licydae, Artiidae and Tenebrionidae families, was noticed. The foliage illness Olivea tectonae and the one caused by Colletotrichum sp., were the most important during the rainy season. Another outstanding illness at this time was the sprout burning caused by Ceratocystis sp. and root rotting by Phythopthora spp. In the dry season when the defoliation occurred, this was caused by leave-eater larvae, Hemileuca maia Drury (Col.: Cerambycidae), crickerts, Schistocercu spp. (Hort.: Acrididae), sap suckers, namely the white fly, Bemisia tabaci (Hom.: Aleyrodidae). The plague with the highest incidence in this period was the teak tree driller, Oberea tripunctata (Col.: Cerambycidae) the damage clearly identified in the infested trees was the sawdust seen at the base of the stems. In the rainy season a high incidence of aphids, or plant lice was detected, Hyadaphis erysimi (Hem.-Hom.: Aphydidae) but the damage caused by the insects was not established. Colletotrichum sp.; was the illness with the highest incidence in the rainy period. However the damage caused by this plague was light. In the season, the plague that showed the highest incidence was the leave-eater caterpillar, Hemileuca maia Drury (Lep.: Saturniidae), since it used up the teak leaves causing foliage loss, however the damage caused by this plague was light. At foliage level Olivea tectonae was the plague which showed a high incidence of affectation, being able to cover the entire canopy foliage area, showing a high level of severity although premature defoliation caused by the plague was not detected. At vascular level, the highest incidence level of affectation and severity was caused by Ceratocystis sp.